Corrigendum to “Passive versus active afforestation of agricultural land: Two decades of impacts on tree biomass and ecosystem carbon storage” [For. Ecol. Manage. 1 – May 27, 2026] - Sachin Timilsina; David Bille Byriel; Nathan Le Boursicaud; Davide Barsotti; Yamina Micaela Rosas; Anna Karina Zimmermann; Torben Riis-Nielsen; Inger Kappel Schmidt; Lars Vesterdal; Per Gundersen; Raphaël J. Manlay; Sebastian Kepfer-Rojas (Forest Ecology and Management, 2026)

Passive versus active afforestation of agricultural land: Two decades of impacts on tree biomass and ecosystem carbon storage - Sachin Timilsina; David Bille Byriel; Nathan Le Boursicaud; Davide Barsotti; Yamina Micaela Rosas; Anna Karina Zimmermann; Torben Riis-Nielsen; Inger Kappel Schmidt; Lars Vesterdal; Per Gundersen; Raphaël J. Manlay; Sebastian Kepfer-Rojas (Forest Ecology and Management, 2026)

Soil organic carbon sequestration over 50 years in resampled afforestation chronosequences on former cropland - Ming Yu; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Teresa G. Bárcena; Inger Kappel Schmidt; Per Gundersen; Ludovica D'Imperio; Carsten W. Mueller; Lars Vesterdal (Journal of Environmental Management, 2026)

Understory vegetation development along 60-year chronosequences of oak, beech, and Norway spruce - Davide Barsotti; Sebastian Kepfer-Rojas; Yamina Micaela Rosas; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; Inger Kappel Schmidt (Forest Ecology and Management, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Structural diversity, tree species richness and biomass production in new forests on agricultural land - Yamina M. Rosas; Inger Kappel Schmidt; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; David Bille Byriel; Mathias Just Justesen; Davide Barsotti; Sebastian Kepfer-Rojas (Remote Sensing of Environment, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Can triad forestry reconcile Europe’s biodiversity and forestry strategies? A critical evaluation of forest zoning - Thomas A. Nagel; Mariano Rodríguez-Recio; Tuomas Aakala; Per Angelstam; Admir Avdagić; Zbigniew Borowski; Andrés Bravo-Oviedo; Gediminas Brazaitis; Thomas Campagnaro; Michał Ciach; Milic Curovic; Inken Doerfler; et al. (Ambio, 2025)
Balancing increasing demand for wood products while also maintaining forest biodiversity is a paramount challenge. Europe’s Biodiversity and Forest Strategies for 2030 attempt to address this challenge. Together, they call for strict protection of 10% of land area, including all primary and old growth forests, increasing use of ecological forestry, and less reliance on monocultural plantations. Using data on country wide silvicultural practices and a new database on strict forest reserves across Europe, we assess how triad forest zoning could help meet these goals. Our analysis reveals that zoning in Europe is overwhelmingly focused on wood production, while there has been little concomitant protection of forests in strict reserves. Moreover, most strict forest reserves are

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

One to rule them all? Assessing the performance of sustainable forest management indicators against multitaxonomic data for biodiversity conservation - Yoan Paillet; Livia Zapponi; Peter Schall; Jean-Matthieu Monnet; Christian Ammer; Lorenzo Balducci; Steffen Boch; Gediminas Brazaitis; Alessandro Campanaro; Francesco Chianucci; Inken Doerfler; Markus Fischer; et al. (Biological Conservation, 2024)

Beyond species richness: Forest structure and edaphic conditions have similar importance but different effects on multi-taxon biodiversity - Sebastian Kepfer-Rojas; Otso Ovaskainen; Peter Friis Møller; Vivian Kvist Johannsen; David Bille Byriel; Mathias Just Justesen; Torben Riis-Nielsen; Aslak Kappel Hansen; Lasse Gottlieb; Inger Kappel Schmidt (Forest Ecology and Management, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Land-use effects on leaf-litter breakdown in streams in a tropical lowland catchment - Oscar Alberto Rojas-Castillo; Sebastian Kepfer-Rojas; Dean Jacobsen (Aquatic Sciences, 2024)
The expansion of oil palm and cattle grazing in the tropics continues to alter numerous ecosystem functions. The generated land-use change is potentially impacting stream leaf-litter breakdown, a fundamental process for freshwater ecosystems. To assess the effect of land-use change, we studied breakdown rates of forest ( Pachira aquatica , Pouroma aspera , Sloanea ampla , and Hippocratea volubilis ) and oil palm ( Elaeis guineensis ) leaves after a 26-day immersion in streams surrounded by rainforests, grazing lands, or oil palm plantations with and without riparian buffers. In addition, we assessed breakdown drivers by deploying litter bags (248) of two mesh sizes (15 mm and 0.5 mm) allowing or restricting macroinvertebrates’ access (134 coarse-mesh bags and 114 fine-mesh bags). Forest leaf breakdown by microbes (fine-mesh) was lower by 55% in the plantations compared to forests; while microbial oil palm-leaf breakdown was lower by 32% in the unbuffered plantations compared to forests ( p p > 0.05) in the plantations but not when these preserved riparian buffers. Litter breakdown was driven primarily by microbes in all land uses except in the buffered plantations, possibly due to increased shredder biomass. These results suggest that oil palm agriculture may decrease microbial stream leaf-litter breakdown, especially in streams with no riparian buffers.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Meta‐analysis contrasting freshwater biodiversity in forests and oil palm plantations with and without riparian buffers - Oscar Alberto Rojas‐Castillo; Sebastian Kepfer Rojas; Leandro Juen; Luciano Fogaça de Assis Montag; Fernando Geraldo Carvalho; Thiago Pereira Mendes; Kenny Wei Jie Chua; Clare L. Wilkinson; Mohammad Noor Azmai Amal; Muhammad Fahmi‐Ahmad; Dean Jacobsen (Conservation Biology, 2024)
The expansion of oil palm plantations has led to land‐use change and deforestation in the tropics, which has affected biodiversity. Although the impacts of the crop on terrestrial biodiversity have been extensively reviewed, its effects on freshwater biodiversity remain relatively unexplored. We reviewed the research assessing the impacts of forest‐to‐oil palm conversion on freshwater biota and the mitigating effect of riparian buffers on these impacts. We searched for studies comparing taxa richness, species abundance, and community composition of macroinvertebrates, amphibians, and fish in streams in forests (primary and disturbed) and oil palm plantations with and without riparian buffers. Then, we conducted a meta‐analysis to quantify the overall effect of the land‐use change on the 3 taxonomic groups. Twenty‐nine studies fulfilled the inclusion criteria. On average, plantations lacking buffers hosted 44% and 19% fewer stream taxa than primary and disturbed forests, respectively. Stream taxa on plantations with buffers were 24% lower than in primary forest and did not differ significantly from disturbed forest. In contrast, stream community composition differed between forests and plantations regardless of the presence of riparian buffers. These differences were attributed to agrochemical use and altered environmental conditions in the plantations, including temperature changes, worsened water conditions, microhabitat loss, and food and shelter depletion. On aggregate, abundance did not differ significantly among land uses because increases in generalist species offset the population decline of vulnerable forest specialists in the plantation. Our results reveal significant impacts of forest‐to‐oil palm conversion on freshwater biota, particularly taxa richness and composition (but not aggregate abundance). Although preserving riparian buffers in the plantations can mitigate the loss of various aquatic species, it cannot conserve primary forest communities. Therefore, safeguarding primary forests from the oil palm expansion is crucial, and further research is needed to address riparian buffers as a promising mitigation strategy in agricultural areas.

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Contrasting responses of multiple insect taxa to common heathland management regimes and old-growth successional stages - David Bille Byriel; Hjalte Ro-Poulsen; Sebastian Kepfer-Rojas; Aslak Kappel Hansen; Rikke Reisner Hansen; Mathias Just Justesen; Emil Kristensen; Cecilie Bülow Møller; Inger Kappel Schmidt (Biodiversity and Conservation, 2023)
Maintaining heathlands in early successional stages to sustain heather ( Calluna vulgaris ) is a common, large-scale management practice in Europe. However, allowing patches of long-term natural vegetation development may increase habitat heterogeneity benefitting insects, but empirical evidence is sparse. We investigated how old-growth heathland (> 30 years abandonment) affect species richness and composition of bees (Anthophila), crane flies (Tipuloidea), ground beetles (Carabidae), hoverflies (Syrphidae) and rove beetles (Staphylinidae) in relation to their hygropreference. Adult insects, vegetation and edaphic explanatory variables were collected in old-growth, managed and wet sites and compared in four lowland heathland locations in Denmark. We found 299 species including 24 nationally red-listed. Species composition differed between managed, old-growth and wet heathland for all taxa. Indicator species and richness analyses showed a predominance of xerophilic bee species in managed heathland. Old-growth heathland showed a predominance of mesophilic indicator species, and higher richness of mesophilic crane flies and of hygrophilic ground and rove beetles compared to managed heathland. Wet heathland was generally dominated by hygrophilic species. Soil moisture, bare soil and vegetation height density were important drivers explaining the contrasting responses in richness and composition between heathland types. Our results demonstrate that heathland management focusing solely on early successional vegetation stages may homogenize insect communities. We suggest that management practices should focus on improving structural vegetation heterogeneity. This can be achieved through management regimes that reset the succession and expose bare soil, but also by allowing patches of old-growth vegetation stages to develop and by conserving existing ones.

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)